Effect of X-ray irradiation on hepatocarcinoma cells and erythrocytes in salvaged blood - Feng-Jiang Zhang (Nature Portfolio, 2017)
Abstract The broad clinical acceptance of intraoperative blood salvage and its applications in cancer surgery remain controversial. Until now, a method that can safely eliminate cancer cells while preserving erythrocytes does not exist. Here, we investigated whether X-ray generated from linear accelerator irradiation at a certain dose can kill hepatocarcinoma cells while preserving erythrocytes. HepG2, SK-Hep1 or Huh7 cells were mixed into the aliquots of erythrocytes obtained from healthy volunteers. After the mixed cells were exposed to 30 Gy and 50 Gy X-rays irradiation, the viability, clonogenicity, DNA synthesis and tumorigenicity of the tumor cells were determined by the MTT assay, plate colony formation, 5-ethynyl-2′-deoxyuridine incorporation, and subcutaneous xenograft implantation into immunocompromised mice. The ATP, 2,3-DPG, free Hb, osmotic fragility, blood gas variables in erythrocytes and morphology of erythrocytes at 0 h, 12 h, 24 h, 48 h, 72 h after irradiation were analyzed. X-ray irradiation at 30 Gy effectively inhibited the viability, proliferation, and tumorigenicity of HepG2, SK-Hep1 and Huh7 cells without noticeably damaging the ability of oxygen-carrying, membrane integrity and morphology of erythrocytes. Theses results suggest that X-ray at 30 Gy irradiation might be safe to eliminate hepatocarcinoma cells while preserving erythrocytes in salvaged blood.